Improved hybrid scrubbing scheme for spaceborne static random access memory‐based field programmable gate arrays. Issue 19 (17th July 2019) - Li, Yue; Chen, Zhichun; Shen, Yuyao; Wang, Yongqing
Abstract : With the shrinking feature sizes of static random access memory‐based field programmable gate arrays (FPGAs), the occurrence probability of multiple‐cell upsets (MCUs) in FPGAs continues to increase. This reduces the reliability of FPGAs. This article proposes an improved hybrid scrubbing scheme to solve this problem. Based on the conventional hybrid scrubbing scheme, the error detection process is improved by changing the error correction object from an erroneous frame to an erroneous zone. MCUs can be rapidly corrected through continuous error detection and erroneous zone correction. The theoretical analysis and implementation results show that the improved hybrid scrubbing scheme can effectively reduce the average repair time of MCU errors.